The Implementation of Bicycle Lanes in Pekanbaru City - Zaini, Abdul Kudus; Fadillah, Muhammad Arif; Muttaqin, Muhammad Zainal (International Journal of Multidisciplinary Approach Research and Science, 2024)
The concept of fostering environmentally conscious urban environments has emerged as a pivotal strategy in mitigating the escalating pace of developmental endeavors. A prominent approach entails the adoption of eco-friendly transportation modalities, prominently featuring non-motorized conveyance options. A tangible stride towards the realization of eco-centric urban landscapes lies in the alteration of societal lifestyles, thereby cultivating heightened environmental consciousness. Across various locales in Indonesia, the prevalent trajectory towards eco-friendly living is epitomized by the widespread embrace of bicycling as a quintessential means to augment communal mobility. This burgeoning proclivity has engendered the establishment of dedicated bicycle infrastructure within urban landscapes, exemplified by communal cycling initiatives and the institution of “Car Free Day” initiatives. Moreover, Pekanbaru City—characterized by its distinctive topography, climate dynamics, and idiosyncratic urban features—presents a distinct milieu that accentuates the complexities entailed in orchestrating widespread bicycle utilization. Therefore, the objective of this study is to explore how the deployment of bicycle lanes can be tailored to accommodate the community’s demands for bicycle usage, the demographics of bicycle users, and the appropriateness of bicycle lane integration.